2014
DOI: 10.4025/actasciagron.v37i1.18088
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effects of the hydrogen potential and fungicide treatment on Pitaya seed germination

Abstract: ABSTRACT. The objective of the present study was to evaluate pitaya seed germination under different hydrogen potentials, with or without fungicide treatment. A completely randomized design was employed under a 3 x 13 x 2 factorial scheme, corresponding to three pitaya species (white pitaya, pitaya hybrid I, pitaya hybrid II), thirteen hydrogen potentials (3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, and 9.0) and two fungicide conditions (presence and absence), with four replications. The perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
(4 reference statements)
1
9
1
Order By: Relevance
“…From the few studies considering the pH effect on the germination process, it has been observed that pH levels between 3.0 and 11.0 in Lactuca sativa (Wandscheer et al, 2011) and between 3.0 and 9.0 in Hylocereus spp. (Ortiz et al, 2015) has not significantly influenced the percentage of germination. However, Ortiz et al (2015) found a significant effect of pH on vigor, expressed by GSI, in one of the three genotypes of Hylocereus spp.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…From the few studies considering the pH effect on the germination process, it has been observed that pH levels between 3.0 and 11.0 in Lactuca sativa (Wandscheer et al, 2011) and between 3.0 and 9.0 in Hylocereus spp. (Ortiz et al, 2015) has not significantly influenced the percentage of germination. However, Ortiz et al (2015) found a significant effect of pH on vigor, expressed by GSI, in one of the three genotypes of Hylocereus spp.…”
Section: Introductionmentioning
confidence: 76%
“…(Ortiz et al, 2015) has not significantly influenced the percentage of germination. However, Ortiz et al (2015) found a significant effect of pH on vigor, expressed by GSI, in one of the three genotypes of Hylocereus spp. evaluated, with lower performance at pH 4.0; 5.0 and 6.0.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…After the incubation period, the solution was sieved under running water to eliminate pulp residues and preserve the seeds, which were then placed on filter paper and shade dried at room temperature for 48 h (ORTIZ et al, 2015).…”
Section: Methodsmentioning
confidence: 99%